Variability of factors influencing coffee export performance in Indonesia. - Yanuarti, Rizky; Widjaya, Dani (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
Abstract Empirical evidence is lacking on the nexus between coffee commodity output and commodity price volatility of developing countries especially during pandemic era. The most visible impact from an economic perspective is the change of price expectation on people's basic needs which are in line with the decline of economic growth in Indonesia. This has significant implications, particularly considering the important role of coffee in supporting the country's economy. The aim of this study is to examine the factors that influence the performance of coffee exports in Indonesia. The novelty of this study lay on the used national dataset within the range of 20 years (2000-2020) and including the pandemic effect on coffee sector performance. We examines the relationship between variables and coffee exports in Indonesia using unit root tests, cointegration analysis, and an Error Correction Model (ECM). The results show that coffee exports, total area, coffee production, coffee price, gross national income, and coffee imports have significant influences on coffee exports. The variables of total area and coffee production impact coffee exports negatively in the long term, while coffee price, gross national income, and coffee imports have mixed effects. In the short term, total area and coffee production significantly affect coffee exports, while coffee prices and gross national income show no significant impact. Coffee imports have a significant negative influence on coffee exports in the short term. These findings contribute to understanding the dynamics of the coffee industry in Indonesia.